Development of a Smartphone Application “Family Care Stunting” to Increase the Independence of Families with Stunting Toddlers and Comorbid Diseases - Anita Dyah Listyarini; Oktia Woro Kasmini Handayani; Ari Yuniastuti; Eko Farida (Jurnal Kesehatan Masyarakat, 2025)
Stunting is a complex public health problem in Indonesia. The incidence of stunting in Kudus City was 3,601 toddlers (5.85%), with the highest prevalence in Dawe District (13.32%), Undaan District (11.13%), Gebog District (10.66%), and 238 children under five, accompanied by comorbidities such as acute respiratory tract infections (ARI), diarrhea, tuberculosis (TB), and worms. One of the determining factors for success in combating stunting is family independence in managing the health of toddlers. However, family independence is constrained by limited access to information, lack of balanced nutrition education, sanitation, personal hygiene, symptoms of comorbidities, monitoring and development of toddlers not routinely, non-compliance with immunization and treatment. Smartphone applications can be used to overcome these obstacles. This study aims to develop and evaluate the effectiveness of the “Family Care Stunting” smartphone application in improving the health independence of families of stunted toddlers with comorbidities. This study used a research and development design, with 201 respondents from families of stunted toddlers who had comorbidities. Effectiveness was analyzed using the Wilcoxon nonparametric differential test to compare the level of family health independence before and after the intervention. There was a significant increase in the level of family health independence after the intervention of the “Family Care Stunting” smartphone application (p-value = 0.000). This application has the potential to be an innovative tool that supports families to play an active role in child health management, thereby contributing to more comprehensive stunting prevention and handling efforts.